First record of Hyalascus (Hexactinellida: Rossellidae) from the Indian Ocean, with description of a new species from a volcanic seamount in the Andaman Sea - Sautya, Sabyasachi; Tabachnick, Konstantin R.; Ingole, Baban (Zootaxa, 2010)
A new species of Hyalascus is described from the submarine volcanic crater seamount of Andaman Back-arc Basin, Indian Ocean. The genus was previously known in the Pacific Ocean only.